Brain-based teaching with adolescent learning in mind - Crawford, Glenda Beamon (Corwin Press, a Sage Publications Company, 2007)
Presents the newest research on the adolescent brain and offers a framework for linking brain-based teaching to students' social, emotional, and cognitive needs.